The significance of changes in platelet concentration during the early phase after severe burn injury in a Chinese mass casualty. Issue 1 (6th December 2017) - Shou, Beiming; Li, Junqiang; Tang, Chenqi; Tan, Qian; Zheng, Dongfeng; Sun, Binwei; Nie, Lanjun; Zhang, Hongwei; Jiang, Yanan; Wang, Chunming; Wu, Yanwen
Abstract: Background: Changes in platelet concentration are common in severe burn patients. Platelets play a key role in the course of disease. This study aims to explore the significance of platelet concentration during the course of the disease in victims of a mass burn casualty. Methods: A total of 180 patients were involved in the "8.2" Kunshan explosion accident in China. The examined data included age, gender, total burn area (% TBSA), third-degree burn area (% TBSA), and platelet concentration within the first 5 days after the burn injury. The patients were divided into two groups according to four indicators (resuscitation, acute respiratory distress syndrome, acute kidney injury, septic shock). We collected several types of data for the patients and divided the patients into a complication group and non-complication group according to the diagnostic criteria. We analyzed the platelet concentration of the two groups using t tests to determine whether significant differences were present. P values < 0.05 were considered statistically significant. Results: The group with successful resuscitation had higher platelet concentration than the failure group on day 3 and day 5. The patients who suffered from acute kidney injury (AKI) and septic shock had a lower platelet concentration than non-sufferers on day 3 and day 5. Conclusions: The platelet concentration of burn patients can dynamically reflect the pathophysiological changes of the body. It can be used as an early objective indicator of prognosis in mass burn casualty cases.